Digital Transformation of Informal Workers in the New Normal Era: “Can It Be the Solution We Are Searching For?” - Suryo Adi Rakhmawan (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2022)
The COVID-19 pandemic has proven to accelerate digitalisation transformation in Indonesia. Various economic activities have involved digital media, the internet, and information technology to support productivity, including informal workers who make up the majority of workers in East Java. This research can provide an initial picture of digital transformation and its impact on informal workers in the new normal through the National Labor Force Survey Data from 2019 to 2022, complemented by other data. Using binary logistic regression analysis, all independent variables in the form of digitalisation, social security, productive age, and risk of exposure to COVID-19 proved to have a significant effect on the welfare of informal workers in the new normal. Furthermore, with the focus of the analysis on digitisation, this study shows that digitalisation can significantly catalyse the formalisation of the informal workforce. The formalisation will reduce the vulnerability of informal workers so that microeconomic activity can be accelerated, which impacts the macroeconomy and society in East Java. This study can also describe the specific segmentation of regencies/cities in East Java regarding the readiness for digitalisation transformation as measured by analysis of variable factors related to the demand and supply sides of digital transformation. Both sides were then carried out a cluster analysis of the Regency/City area in East Java.